Formononetin: A Review of Its Anticancer Potentials and Mechanisms - Tay, Kai-Ching; Tan, Loh Teng-Hern; Chan, Chim Kei; Hong, Sok Lai; Chan, Kok-Gan; Yap, Wei Hsum; Pusparajah, Priyia; Lee, Learn-Han; Goh, Bey-Hing (Frontiers in Pharmacology, 2019)
Cancer, a complex yet common disease, is caused by uncontrolled cell division and abnormal cell growth due to a variety of gene mutations. Seeking effective treatments for cancer is a major research focus as the incidence of cancer is on the rise and drug resistance to existing anti-cancer drugs is major concern. Natural products have the potential to yield unique molecules and combinations of substances that may be effective against cancer with relatively low toxicity/better side effect profile compared to standard anticancer therapy. Drug discovery work with natural products has demonstrated that natural compounds display a wide range of biological activities correlating to anticancer effects. In this review, we discuss formononetin (C16H12O4), which originates mainly from red clovers and the Chinese herb Astragalus membranaceus. The compound comes from a class of 7-hydroisoflavones with a substitution of methoxy group at position 4. Formononetin elicits antitumourigenic properties in vitro and in vivo by modulating numerous signaling pathways to induce cell apoptosis (by intrinsic pathway involving Bax, Bcl-2 and caspase-3 proteins), cell cycle arrest (by regulating mediators like cyclin A, cyclin B1 and cyclin D1), and suppress cell proliferation (by STAT activation, PI3K/AKT and MAPK signaling pathway) and inhibit cell invasion (by regulating growth factors VEGF and FGF2, and MMP-2 and MMP-9 proteins). Co-treatment with other chemotherapy drugs such as bortezomib, LY2940002, U0126, sunitinib, epirubicin, doxorubicin, temozolomide and metformin enhance the anticancer potential of both formononetin and the respective drugs through synergistic effect. Compiling the evidence thus far highlights the potential of formononetin to be a promising candidate for chemoprevention and chemotherapy.